Research Paper: Immediate Effects of Lumbosacral Belt on Postural Control During Challenging Tasks in Patients With Chronic Low Back Pain - Masoud Ghofrani; Gholamreza Olyaei; Saeed Talebian; Hossein Bagheri; Kazem Malmir; Shiva Mousavi (Journal of Modern Rehabilitation, 2017)
Introduction: Chronic Low Back Pain (CLBP) may be associated with impaired proprioception which can result in joint instability and balance deficit. However, wearing a lumbosacral belt may be helpful in this situation. This study aimed to identify postural control impairments in patients with CLBP and determine the effect of lumbosacral support on postural control strategies in these patients. Materials and Methods: A total of 16 patients with CLBP and 16 healthy subjects participated in this study. Center of Pressure (COP) data were recorded for 30 seconds while wearing or not wearing a belt in four standing positions; double leg with open eyes, double leg with closed eyes, single leg with open eyes, single leg with closed eyes. Postural control was assessed using range, area and total mean velocity for each experimental condition. Results: Patients with CLBP showed significantly larger mean COP range and mean area compared to the healthy controls in single leg stance with closed eyes (P<0.05). Lumbosacral belt reduced significantly mean COP range, mean COP area and mean total velocity during challenging conditions (P<0.05). Conclusion: Individuals with CLBP had poorer postural control compared to the healthy controls as determined by changes in COP. Lumbosacral belt can improve postural control during challenging tasks.